INVESTIGATING THE ROLE OF R8 GENE IN LATE BLIGHT RESISTANT CULTIVAR KUFRI GIRDHARI AND ITS MALE PARENTS - KARDILE, HEMANT Balasaheb (Potato Journal, 2019)
ABSTRACT: Resistance gene analog, R8 has the potential to provide the broad-spectrum resistance to late blight in Solanum demissum. Mining of the potato genome has identified the twelve paralogos with conserved NB-ARC domain. Evolutionary relationship of R8 in potato and its homologous genes in other solanaceae crops showed close relation among primary hosts than secondary hosts of Phytopthora infestans. Late blight is a common disease and caused tremendous yield loss. In order to avoid the yield loss, the resistance cultivars have been developed. Among this Indian potato cultivar, Kufri Girdhari ishighly resistant to the late blight and underlying mechanism of resistance is poorly understood. With this view, we studied the expression profile of R8 gene in response to late blight in Kufri Girdhari along with susceptible cultivar Kufri Bahar. Kufri Girdhari was developed by pollinating the Kufri Megha with bulk pollen from ten genotypes. To identify the exact male parent of Kufri Girdhari the SSR fingerprint analysis were performed along with qRT-PCR analysis. The results of these experiments showed CP3789 is the probable male parent of Kufri Girdhari. Our analysis showed that the R8 gene is present in the pedigree of Kufri Girdhari, and the level of expression was more in five accessions, mainly CP2132, CP2175, CP2366, CP3268, and CP3789 and same could be used for the targeted breeding programme for the development of late blight resistance varieties.